Intoducing a new learning methodology: Are the students ready? - Ismail, Khadijah (2010)
E-learning is proven a successful online-based education mechanism implemented in higher learning institutions especially to cater the rapid increase in the number of enrolled students each year. This paper concerns with the student’s readiness for the introduction of e-learning as a new learning methodology in teaching and learning environment at Universiti Pertahanan Nasional Malaysia (UPNM). Data collection is completed by distributing questionnaires among 197 respondents and descriptive analysis using the data is performed using SPSS 11. Discussions on several selfassessment factors influencing e-learning readiness based on students’ academic profiles are included.